Coastal risk management in a changing climate - Zanuttigh, Barbara (Amsterdam : Butterworth-Heinemann, 2015)
'Existing coastal management and defense approaches are not well suited to meet the challenges of climate change and related uncertanities. Professionals in this field need a more dynamic, systematic and multidisciplinary approach. Written by an international group of experts, Coastal Risk Assessment and Mitigation in a Changing Climate provides innovative, multidisciplinary best practices for mitigating the effects of climate change on coastal structures. Based on the Theseus program, the book includes eight study sites across Europe, with specific attention to the most vulnerable coastal environments such as deltas, estuaries and wetlands, where many large cities and industrial areas are located'--
Includes bibliographical references : pages 613 -628 and index.
Keywords: Coastal zone management -- Case studies; Coast changes -- Risk assessment -- Case studies; Climatic changes -- Risk assessment -- Case studies; Coastal engineering -- Case studies